Blizzard: Fast, Cloud-scale Block Storage for Cloud-oblivious Applications - Mickens, James; Nightingale, Edmund B; Elson, Jeremy; Nareddy, Krishna; Gehring, Darren (Proceedings of NSDI, 2014)
Blizzard is a locality-oblivious, high-performance block store that exposes cloud storage to cloud-oblivious POSIX and Win32 applications. Blizzard connects clients and servers using a network with full-bisection bandwidth, allowing clients to access any remote disk as fast as if it were local. Using a novel striping scheme, Blizzard exposes high disk parallelism to both sequential and random workloads; also, by decoupling the durability and ordering requirements expressed by flush requests, Blizzard can commit writes out-of-order, providing high performance and crash consistency to applications that issue many small, random IOs. Blizzard’s virtual disk drive, which clients mount like a normal physical one, provides maximum throughputs of 1200 MB/s, and can improve the performance of unmodified, cloud-oblivious applications by 2x–10x. Compared to EBS, a commercially available, state-of-the-art virtual drive for cloud applications, Blizzard can improve the SQL server IOp rate by seven-fold while still providing crash consistency.